Multigene phylogenetic characterisation of Colletotrichum artocarpicola sp. nov. from Artocarpus heterophyllus in northern Thailand - Bhunjun, Chitrabhanu S.; Jayawardena, Ruvishika S.; Wei, De-Ping; Huanraluek, Naruemon; Abeywickrama, Pranami D.; Jeewon, Rajesh; Monkai, Jutamart; Hyde, Kevin (Phytotaxa, 2019)
A new species, Colletotrichum artocarpicola, on Artocarpus heterophyllus from Chiang Rai, Thailand, is introduced using both morphological and molecular approaches. Combined phylogenetic analysis of ITS, GAPDH, CHS-1, ACT and TUB2 sequence data demonstrate that Colletotrichum artocarpicola is a distinct species within the gloeosporioides species complex. The new species is illustrated and compared with related taxa, and evidence of its pathogenicity is provided.